Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s10664-017-9554-9
|View full text |Cite
|
Sign up to set email alerts
|

On the reaction to deprecation of clients of 4 + 1 popular Java APIs and the JDK

Abstract: Application Programming Interfaces (APIs) are a tremendous resource-that is, when they are stable. Several studies have shown that this is unfortunately not the case. Of those, a large-scale study of API changes in the Pharo Smalltalk ecosystem documented several findings about API deprecations and their impact on API clients. We extend this study, by analyzing clients of both popular third-party Java APIs and the JDK API. This results in a dataset consisting of more than 25,000 clients of five popular Java AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…In a large-scale study, Robbes et al [6] assess the impact of API deprecation in a Smalltalk ecosystem. Recently, the authors also evaluated the impact in the context of the Java programming language [43], [44]. In this study, they found that some API deprecation have large impact on the ecosystem under analysis and that the quality of deprecation messages should be improved.…”
Section: Studies On Api Evolutionmentioning
confidence: 99%
“…In a large-scale study, Robbes et al [6] assess the impact of API deprecation in a Smalltalk ecosystem. Recently, the authors also evaluated the impact in the context of the Java programming language [43], [44]. In this study, they found that some API deprecation have large impact on the ecosystem under analysis and that the quality of deprecation messages should be improved.…”
Section: Studies On Api Evolutionmentioning
confidence: 99%
“…The trade-off between healthy levels of diversity in a system (here, the Maven Central ecosystem) and the challenges of redundancy and noise is necessary and very natural. Biological studies insist on the importance of keeping less fit or even unexpressed genes as genetic material that is necessary in order to adapt to unpredictable environmental changes [21], [22]. Our study reveals that the immutability of Maven artifacts provides the material for libraries to eventually fit the needs of various users, which eventually results in the emergence of diverse popular and timely versions.…”
Section: A Supporting the Emergence Of Software Diversitymentioning
confidence: 87%
“…Prior studies [5], [6] found that Android is evolving at an average rate of 115 API updates per month. Such evolution may entail arbitrary release schedules and API deprecation durations and may involve removing functionality without prior warning [7]. Therefore, users must regularly study the changes to existing APIs and decide whether they need to migrate their code to adopt the changes.…”
Section: Introductionmentioning
confidence: 99%